2022
DOI: 10.15386/mpr-2526
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome modulation in the prevention and management of colorectal cancer: a systematic review of clinical interventions

Abstract: Introduction. The role of probiotics/prebiotics in modulating the procarcinogenic effects of microbiota have been studied with inconclusive results. This systematic review aimed to identify the role of several studied interventions on the gut microbiota modulation in humans for the prevention and management of colorectal cancer (CRC). Methods. We conducted a systematic search using PubMed and Cochrane Central electronic databases, identifying clinical studies published within the last 20 years. We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Out of the 96 reports that were selected for full-text review, 22 of them were not obtainable. We assessed the eligibility of all 74 articles and identified only 20 systematic reviews and meta-analyses that met our inclusion criteria for the final synthesis [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Figure 1 represents the PRISMA flow diagram with a detailed search and selection process overview.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 96 reports that were selected for full-text review, 22 of them were not obtainable. We assessed the eligibility of all 74 articles and identified only 20 systematic reviews and meta-analyses that met our inclusion criteria for the final synthesis [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Figure 1 represents the PRISMA flow diagram with a detailed search and selection process overview.…”
Section: Search Resultsmentioning
confidence: 99%
“…FIGURE 2: Matrix heatmap of included reviewsAlhhazmi et al[12]; Amitay et al[13]; Anandakumar et al[14]; Aprile et al[15]; Borges-Canha et al[16]; Costa et al[17]; Eastmond et al[18]; Fratila et al[19]; Gethings-Behncke et al[20]; Hussan et al[21]; Karimi et al[22]; Mohammad et al[23]; Negrut et al[24]; Peng et al[25]; Ranjbar et al[26]; Tabowei et al[27]; Valciukiene et al[28]; Vorstenbosch et al[29]; Yu et al[30]; Zwezerijnen-Jiwa et al[31] …”
mentioning
confidence: 99%
“…In CRC treatment, prebiotics and probiotics, as microbiota modulators, play a significant role. They are capable of inhibiting epithelial cell proliferation, reversing DNA damage, and reducing complications from surgery or chemotherapy ( 95 ). A systematic review involving 23 randomized controlled trials (RCTs) showed that supplementing CRC patients with probiotics, including Bifidobacteria and Lactobacilli, improves quality of life, reduces postoperative infections, inhibits the production of pro-inflammatory cytokines, and alleviates chemotherapy side effects, thereby improving surgical outcomes and reducing mortality risk ( 96 ).…”
Section: Polysaccharides Strengthen the Intestinal Defensementioning
confidence: 99%
“…Specific postbiotics, such as SCFAs and the p40 protein produced by Lactobacillus rhamnosus, have been identified as crucial in preventing CRC development. [121,122] SCFAs regulate gene expression, induce apoptosis in cancer cell lines, and contribute to mucosal protection, while the p40 protein aids in reducing intestinal epithelial inflammation and increasing IgA production. [121,122] Although the use of postbiotics shows promise in CRC prevention, further research is also required to confirm their potential.…”
Section: Postbioticsmentioning
confidence: 99%